Lattice of superconducting multilayer nanotubes as ideal high-temperature superconductor - Pokropivny, V.V.; Makarov, I. M.; Pokropivny, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Combining Little's and Ginzburg's ideas with recent progress in nanotubes research, a novel type of material is advanced as a perspective high-Tc superconductor on base of a close-packed lattice of quasi-1D superconducting nanotubes. Idea is offered that superconducting coaxial multilayer nanotubes of the correlation length in diameter is an ideal and natural trap for pinning of Abrikosov vortex. Nanotube should be layered superconductor, such as LuNiBC. Mechanism of superconductivity was proposed and substantiated quantitatively on base of a whispering mode, which is shown to be responsible for a strong enhancement of electron-phonon interaction and for an increase of critical temperature. Nanocomposite built from such quasi-1D nanotubes when coinciding with vortex lattice provides ideal conditions for the pinning, resonance, distortion, ordering and Little-Parks effects, the joint action of which is suggested to result in synergetic effect increasing the superconductivity. Such quasi-1D nanotubular crystal is proposed to synthesize by template approach using zeolite-like membrane.